Advanced Intelligent Computing Technology and Applications 19th International Conference, ICIC 2023, Zhengzhou, China, August 10-13, 2023, Proceedings, Part II - Huang, De-Shuang.; Premaratne, Prashan; Jin, Baohua; Qu, Boyang; Jo, Kang-Hyun.; Hussain, Abir. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This three-volume set of LNCS 14086, LNCS 14087 and LNCS 14088 constitutes - in conjunction with the double-volume set LNAI 14089-14090- the refereed proceedings of the 19th International Conference on Intelligent Computing, ICIC 2023, held in Zhengzhou, China, in August 2023. The 337 full papers of the three proceedings volumes were carefully reviewed and selected from 828 submissions. This year, the conference concentrated mainly on the theories and methodologies as well as the emerging applications of intelligent computing. Its aim was to unify the picture of contemporary intelligent computing techniques as an integral concept that highlights the trends in advanced computational intelligence and bridges theoretical research with applications. Therefore, the theme for this conference was "Advanced Intelligent Computing Technology and Applications". Papers that focused on this theme were solicited, addressing theories, methodologies, and applications in science and technology.
Evolutionary Computation and Learning -- Swarm Intelligence and Optimization -- Information Security -- Theoretical Computational Intelligence and Applications -- Neural Networks -- Pattern Recognition -- Image Processing -- Biomedical Data Modeling and Mining -- Biomedical Informatics Theory and Methods -- Intelligent Computing in Computational Biology -- Intelligent Computing in Drug Design -- Knowledge Discovery and Data Mining -- Machine Learning -- Natural Language Processing and Computational Linguistics -- Deep learning methods and techniques for medical image analysis -- Intelligent Computing in Computer Vision -- Intelligent Computing in Communication Networks -- Intelligent Data Analysis & Prediction -- Expert Systems -- Reinforcement Learning -- Recent advances in deep learning methods and techniques for medical image analysis.
Keywords: Computational intelligence; Computational Intelligence